Makna Nilai Religius Pati Ka Du'a Bapu Ata Mata Ende Lio dalam Perspektif Ajaran Katolik - Floriana Doa; Intansakti Pius X; Emmeria Tarihoran (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the meaning of religious values ​​in the Pati Ka Du'a Bapu Ata Mata tradition of the Ende Lio community and how this tradition is understood from a Catholic perspective. This tradition is a form of respect for ancestors who are believed to continue to play a role in the lives of their descendants. The study aims to explain the religious meaning, ethical values, and the integration of local traditions with the Catholic faith through an inculturation process. Using qualitative methods through interviews, observations, and literature studies, this study found that the Pati Ka Du'a Bapu Ata Mata tradition contains values ​​of gratitude, solidarity, togetherness, and an awareness of human connection with nature, ancestors, and God. From a Catholic perspective, these values ​​align with teachings on respect for others and the communion of saints, although some elements of the tradition require theological refinement to conform to Catholic principles. These findings suggest that local traditions can serve as a means of deepening faith, strengthening cultural identity, and encouraging harmonious religious practices within the Ende Lio community.